Organisational stress among construction staff in contractors' companies - Mohd Hakim, Husna Nazihah (2024)
Organisational stress is a growing concern in the construction industry, potentially impacting employee well-being and project outcomes. Contractors' staff who faced organisational stress frequently had to deal with overload work, poor financial management problem and poor work environment. This study investigates the factors that cause the organisational stress among contractors' staff, the impacts of organisational stress towards contractors' staff, and ways to reduce organisational stress among contractors' staff. Through a quantitative method, questionnaire surveys which distributed to the construction staff in contractors' companies, the research reveals that some contractors' staff faced organisational stress. Data analysis involved descriptive statistics and frequency distributions. The findings reveal that a significant portion of the respondents experience organisational stress. The most commonly reported stressors include workload, tight deadlines, a poor work environment, a lack of work balance, and a long working hour.